The Effect of Using Kahoot! Application on Junior High School Students’ Vocabulary Achievement in Jember - Afi, Aufa; Tasnim, Zakiyah; Fardhani, Aan Erlyana (English Education Study Program, 2024)
The purpose of this research was testing whether or not Kahoot! Application has a significant effect on students’ vocabulary achievement. Thus, a quasi-experimental research design was applied. This research conducted this study on September – October 2023 and involved 68 students as the sample participants. They were divided into two groups, experimental and control groups. Those classes did vocabulary exercise that given by the researcher. Each exercise asked the students to find the English meaning of certain words. The different of those groups was the treatment. In experimental group, Kahoot! Application was used as the treatment, while the control group did the vocabulary exercises by using regular paper. After did the treatment for three times, each groups had a post-test in the form of multiple-choice. Based on the post-test result, the experimental group got a mean score of 94.65 and 90.26 for the control group. Then, the researcher used SPSS to analyze the data by employing an independent sample t-test to make a valid conclusion. The result showed that the value of Sig. 2-tailed was 0.04, which was lower than 0.05. It could be stated that there was a significant difference between the experimental and the control groups. Therefore, the Kahoot! Application can be used as teaching media for learn vocabulary.